2015
DOI: 10.1136/bjsports-2015-094798
|View full text |Cite
|
Sign up to set email alerts
|

Time loss injuries compromise team success in Elite Rugby Union: a 7-year prospective study

Abstract: Background A negative association between injuries and team success has been demonstrated in professional football, but the nature of this association in elite Rugby Union teams is currently unclear. Aim To assess the association between injury burden measures and team success outcomes within professional Rugby Union teams. Methods A seven-season prospective cohort design was used to record all time-loss injuries incurred by English Premiership players. Associations between team success measures (league points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 21 publications
13
75
1
Order By: Relevance
“…1 Along with the social and economic effects that injuries may have on athletes and their families, 2 injuries are also detrimental to team success in various sports. 3,4 Consequently, it is important to understand the injury epidemiology of a given population in order to effectively plan injury-prevention strategies and minimize the effects of injuries on both the athlete and the team.…”
mentioning
confidence: 99%
“…1 Along with the social and economic effects that injuries may have on athletes and their families, 2 injuries are also detrimental to team success in various sports. 3,4 Consequently, it is important to understand the injury epidemiology of a given population in order to effectively plan injury-prevention strategies and minimize the effects of injuries on both the athlete and the team.…”
mentioning
confidence: 99%
“…The study is being performed in the premier league schools where winning is a priority (a decrease in injuries contributes to winning),52 and therefore, the participants in the intervention group will be motivated to implement the injury prevention measures to the best of their abilities.…”
Section: Randomised Controlled Trial Methodologymentioning
confidence: 99%
“…There is evidence linking injury and team success in several football (soccer) studies,43–45 and a recent 7-year prospective study by Williams et al 46 found that time loss injuries compromised team success in elite rugby. The work by Williams et al aside, it is important to recognise that most of the research into physical loads and injury in rugby to date has been conducted on single teams over short follow-up periods, resulting in low numbers of injuries being available for analysis.…”
Section: Load and Injurymentioning
confidence: 99%